Phytoplankton functional groups associated with the trophic state of tropical reservoirs - Simone Alves de Oliveira; Carla Ferragut; Carlos Eduardo de Mattos Bicudo (Acta Limnologica Brasiliensia)
Abstract: Aim The study investigated functional groups representing reservoirs of different trophic states, identifying eutrophication indicators. Methods Water samples were collected to evaluate physical and chemical characteristics and the phytoplankton composition in five reservoirs during dry and rainy periods. Results Low concentration of dissolved nutrients (nitrite, orthophosphate, and total dissolved phosphorus) and total phosphorus described the oligotrophic and mesotrophic reservoirs, and the opposite for the eutrophic and hypertrophic reservoirs. Twenty-four functional groups were identified, eight of which were considered descriptors due to high biomass. Functional groups were influenced by the trophic state, and secondarily by seasonality. Typical functional groups represented the hypertrophic, eutrophic, and mesotrophic reservoirs. However, an oligotrophic reservoir was represented by a functional group commonly associated with environmental eutrophic. Conclusions The functional groups were representative of the trophic state of systems and detected signs of early eutrophication.